A stranger at my table : the postcolonial story of a family caught in the half-life of empires - Figueiredo, Ivo de, 1966- (DoppelHouse Press, 2018)
A biracial son of a subcontinental, migrant family searches for his estranged father's story and ultimately rewrites his own.